Severe pneumonia of torpid evolutión in a young patient with a negative molecular test for a new coronavirus: Neumonía grave de evolución tórpida en paciente joven con prueba molecular negativa para nuevo coronavirus - Rivera, Josef (2020)
The coronavirus disease originated in the year 2019 (COVID-19), has spread rapidly throughout the world, wreaking havoc on the health system and society. We report the case of a 26-year-old man with a history of asthma and obesity, who returned from the US and went to the emergency room with respiratory symptoms, hypoxemia and interstitial infiltrate on chest radiography, he was admitted to the isolation room The nasopharyngeal swab RT-PCR molecular test was negative, so he was transferred to a common emergency room. Initial management was conservative, however the patient evolved unfavorably requiring ventilatory support, but died on the fifth day of hospitalization. A second positive result for SARS-CoV-2 was received the day after the patient died, being one of the first young victims in Peru.